Career Development Impacts of COVID-19: Practice and Policy Recommendations. (October 2020) - Autin, Kelsey L.; Blustein, David L.; Ali, Saba R.; Garriott, Patton O.
The advent of the COVID-19 pandemic has resulted in drastic changes to employment around the globe. In the present article, we identify four emerging impacts of the pandemic and how career development professionals might respond through policy and practice. Specifically, we focus on four distinct but related domains: unemployment, worker mental health, the work–family interface, and employment disparities. For each domain, we offer recommendations for policy and practice with the hope that career development professionals might reframe the COVID-19 crisis as an opportunity for a renewed commitment to supporting worker well-being.